Strategies to minimize medication errors in emergency units: an integrative review - Debora Bessa Mieiro; Érica Bueno Camargo de Oliveira; Renata Elizabete Pagotti da Fonseca; Vivian Aline Mininel; Sílvia Helena Zem-Mascarenhas; Regimar Carla Machado
ABSTRACT Objective: To assess the strategies used by the Nursing team to minimize medication errors in emergency units. Method: Integrative literature review in the PubMed, BDenf, Cochrane and LILACS databases. Timeless research, without language limitation, performed by peers. Articles published in full that answered the guiding question were included in research. Results: Educational strategies (conducting campaigns, elaborating explanatory manuals, creating a multidisciplinary committee involved in the prevention and reduction of adverse drug events); organizational (meetings, Deviance positive, creation of protocols and changes in the work process) and new technologies (implementation of prescription by computerized system, introduction of the unit doses and of the bar code in the administration of medicines) were evidenced in the studies with the purpose of minimizing medication errors in an emergency unit. Conclusion: The strategies identified were effective in minimizing medication errors in emergency units.